RAPD MOLECULAR MARKERS FOR DIVERSITY ANALYSIS IN WHEAT (TRITICUM SPECIES) - CHANDAN J NINGHOT,; MANISH V BORATKAR,; SATBEER SINGH,; N. R. POTDUKHE, (The Bioscan, 2015)
Molecular diversity was assessed among wheat genotypes by employing molecular markers.In total, 25 RAPD markers amplified 23 fragments with 65.22 % polymorphism. Unweighted pair group method with arithmetic mean (UPGMA) analysis generated by RAPD based on genetic distance estimates displayed two major clusters of wheat genotypes; first group includes fifteen genotypes and the second includes ten genotypes.A Jaccard’s similarity coefficient of all genotypes derived from RAPD data ranged from 0.54 to 0.95.Marker data subjected to analysis of molecular variances revealed more diversity within population.These molecular markers can be put to use for characterization and selection of wheat genotypes